Pengaruh Budaya Organisasi terhadap Kinerja Perawat dengan Disiplin Kerja sebagai Variabel Intervening di RSUD Pesanggrahan - Vernadeth, Verly; Anindita, Rina; Musaida, Musaida (Journal of Hospital Management, 2021)
Human resources is a very important thing for hospitals. Therefore, human resources must have a good quality of performance to achieve the vision and mission of the hospital. The purpose of this study was to analyze the influence of organizational culture on the performance of nurses with work discipline as an intervening variable in RSUD Pesanggrahan. This research is a quantitative study with a causal research design with 44 respondents, conducted from May 2019 to August 2019. Determination of the number of samples using the census method. Research variables are Performance as the dependent variable, Organizational Culture as an independent variable, and Work Discipline as an intervening variable. Collecting data in this study using a questionnaire with technical research instruments using a questionnaire with a 4 level Likert scale. Analyzing data using path analysis. The results showed that the relationship between organizational culture and performance was not significant, organizational culture has a positive and significant influence on work discipline, and organizational culture has an influence on the performance of nurses with work discipline as an intervening variable. Managerial implications that can be applied to improve performance are to increase work discipline and instill a stronger organizational culture.Keywords: nurse performance, organizational culture, work discipline